A first estimation of tsunami hazard of the Pacific coast of Costa Rica from local and distant seismogenic sources - Chacon-Barrantes, Silvia (2021)
Costa Rica has been affected by several local and distant tsunamis in the past, but the historical information is scarce and incomplete. Its Pacific coast stretches for over a thousand kilometers, and tsunami hazard has never been evaluated for its full extent. Numerical modeling of tsunami propagation and inundation is a useful tool to assess tsunami hazard, particularly in cases with limited historical information available. Here, we perform a first estimation of tsunami hazard for the Pacific coast of Costa Rica from seismogenic sources, by numerical propagation of 57 local and distant tsunamis to a depth of 20 m. The results of our study identified tsunami sources that are particularly threatening for Costa Rica and determined locations with higher tsunami hazard. For the analysis, the Pacific coast of Costa Rica was divided into segments and subsegments based on differences in continental slope morphology. Subsegments with higher tsunami heights were Southwest Nicoya Peninsula and West Osa Peninsula, and in a lesser extent North Guanacaste, North Nicoya Peninsula, and Central Pacific. Regions with long and gentle slopes and narrow continental shelf were affected by higher tsunami waves, due to more efficient tsunami energy transmission to the shelf and reduced energy loss while traveling through a narrow shelf. On the opposite, steeper continental slopes reflected most of the tsunami energy, causing smaller tsunami heights nearshore, regardless of the shelf width. Nevertheless, other effects played a major role, like curved coastlines that focused tsunami energy, wave refraction, interference, and trapped edge waves. Distant tsunamis dominated the threat, with tsunamis coming from the Tonga-Kermadec and the Colombia-Ecuador Trenches causing the greatest heights due to directivity, and arrival times of about 15 h and 75 min, respectively. Local tsunamis had short arrival times but a localized impact, mainly at the shoreline in front of the generation region but were also affected by tsunami focusing, wave refraction, and edge waves. Outer rise and Osa sources caused the lowest impact within local sources. These results provide a guide for emergency planners to prioritize coastal locations and tsunami sources for tsunami preparedness actions and warning protocols.